Sąsiedzkość jako typ więzi społecznej i przestrzeń animacyjna - Kluzowicz, Julia (Adult Education Discourses, 2020)
In the face of civilisation and social changes, neighborhood understood in terms of relationships between people living in a given community, consisting of everyday, direct, friendly contact based on trust and cooperation, is atrophy. Whereas, the experience of closeness that is given by a well-organised local community seems extremely important from the point of view of creating civil society. This is known to sociologists and urban planners who have been dealing with housing and neighborhood issues for years, however, in social pedagogy these topics are often marginalised. This gap is filled by social animation, which, acting as part of associations, undertakes a number of initiatives to create community bonds. By characterising the neighborhood in terms of community, specifying its features and distinguishing categories favoring its creation, as well as threats that annihilate it, one could be tempted by even more effective animation activities in this area.